Analysis of the Tensile Strength and Rate of Biodegradability of PVA-Chitosan Blended Plastic Films Using White Shrimp (Litopenaeus setiferus) as Chitosan Source - Lola Domnina Pestaño; Jayvee John Alib; Stephen S. O; Amado Emilio S.J. Palma III (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
Chitin was extracted from white shrimps (Litopenaeus setiferus) and was processed to chitosan by the standard procedures for deproteinisation, demineralisation and multideacetylation. The chitosan product was tested with FTIR for the percentage degree of deacetylation. Chitosan was blended with polyvinyl alcohol in different concentrations (2%, 3% and 4%) to produce biodegradable plastics. The resulting plastics were tested for variation of the blend concentrations in the tensile elongation, which is one of the characteristics needed for their use in food packaging applications. The plastic films’ biodegradability with respect to time was also determined by measuring the weight loss with time during soil burrowing at four different time intervals within a month period (7.5, 7, 7, 7 days). The tensile test results showed that as the chitosan concentration is increased, the plastics showed increasing tensile strength values. Similarly, there was an observed increase in the degree of biodegradability when the film comprises of pure chitosan component.